Inhibition of PDE5 Restores Depressed Baroreflex Sensitivity in Renovascular Hypertensive Rats - Cavalcanti, Clênia de Oliveira; Alves, Rafael R.; Oliveira, Alessandro L. de; Cruz, Josiane de Campos; França-Silva, Maria do Socorro de; Braga, Valdir de Andrade; Balarini, Camille de Moura (Frontiers in Physiology, 2016)
Renal artery stenosis is frequently associated with resistant hypertension, which is defined as failure to normalize blood pressure (BP) even when combined drugs are used. Inhibition of PDE5 by sildenafil has been shown to increase endothelial function and decrease blood pressure in experimental models. However, no available study evaluated the baroreflex sensitivity nor autonomic balance in renovascular hypertensive rats treated with sildenafil. In a translational medicine perspective, our hypothesis is that sildenafil could improve autonomic imbalance and baroreflex sensitivity, contributing to lower blood pressure. Renovascular hypertensive 2-kidney-1-clip (2K1C) and sham rats were treated with sildenafil (45 mg/Kg/day) during 7 days. At the end of treatment, BP and heart rate (HR) were recorded in conscious rats after a 24-hour-recovery period. Spontaneous and drug-induced baroreflex sensitivity and autonomic tone were evaluated; in addition, lipid peroxidation was measured in plasma samples. Treatment was efficient in increasing both spontaneous and induced baroreflex sensitivity in treated hypertensive animals. Inhibition of PDE5 was also capable of ameliorating autonomic imbalance in 2K1C rats and decreasing systemic oxidative stress. Taken together, these beneficial effects resulted in significant reductions in BP without affecting HR. We suggest that sildenafil could be considered as a promising alternative to treat resistant hypertension.